(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Abdulla Qadiri, one of the pioneering figures in Uzbek literature, holds a unique place in the cultural and intellectual history of Central Asia. His work, particularly the novel “Bygone Days” (“O‘tgan Kunlar”), offers profound insights into the complexities of human relationships, social norms, and moral dilemmas. This article explores the themes of wisdom in Bygone Days, analyzing the linguistic and cultural elements that contribute to its enduring legacy. Written in the early 20th century, Bygone Days reflects a period of transition in Uzbek society, marked by the decline of traditional feudal structures and the rise of modernist ideologies. This era witnessed the tension between old and new, with individuals grappling to reconcile deeply rooted customs with emerging societal changes. Qadiri masterfully captured this dynamic, embedding it within the personal and societal conflicts faced by his characters.